Efektivitas Penerimaan Negara Bukan Pajak Usaha Pertambangan Di Kabupaten Manokwari - Juanita R. Horman (Pusat Penelitian Pemberdayaan Fiskal dan Ekonomi Daerah (P3FED) Universitas Papua, 2019)
Non-Tax Revenues are the total of government revenues that are not sourced from general taxation, in which revenue from natural resources become one important source. Manokwari regency has natural resource and coal potentials, that is expected to drive local economy through the utilization of its non-tax revenues. This research aims to calculate the potentials and effectivity of non-tax revenues sourced from mining activities in Manokwari regency. The findings show that non-tax revenue potential is approximately IDR 43.7 billion in 2014, and increases just over IDR 57 billion in 2015. Nevertheless, effectivity of the non-tax revenue derived from mining activities in Manokwari is zero percent, which means ineffective.